2019
DOI: 10.1073/pnas.1821745116
|View full text |Cite
|
Sign up to set email alerts
|

Differential development of large-cell neuroendocrine or small-cell lung carcinoma upon inactivation of 4 tumor suppressor genes

Abstract: High-grade neuroendocrine lung malignancies (large-cell neuroendocrine cell carcinoma, LCNEC, and small-cell lung carcinoma, SCLC) are among the most deadly lung cancer conditions with no optimal clinical management. The biological relationships between SCLC and LCNEC are still largely unknown and a current matter of debate as growing molecular data reveal high heterogeneity with potential therapeutic consequences. Here we describe murine models of highgrade neuroendocrine lung carcinomas generated by the loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
74
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(83 citation statements)
references
References 35 publications
(65 reference statements)
8
74
1
Order By: Relevance
“…In this model, the efficiency of transformation into SCLC as well as tumor latency matched that of mice injected with Ad5-CGRP-Cre, raising the possibility that a subpopulation of K14 + cells in lung is receptive to neuroendocrine transformation. Accordingly, deletion of Rb1 and Trp53 along with Pten and Rbl1 (p107) with Ad5-K5-Cre, which targets cells similar to K14-expressing cells, also led to the development of SCLC, supporting the idea that basal cells can serve as a cell of origin for SCLC in the context of a different set of driver lesions (Lázaro et al 2019).…”
Section: Cell Of Origin Of Small Cell Lung Cancer (Sclc)mentioning
confidence: 79%
See 1 more Smart Citation
“…In this model, the efficiency of transformation into SCLC as well as tumor latency matched that of mice injected with Ad5-CGRP-Cre, raising the possibility that a subpopulation of K14 + cells in lung is receptive to neuroendocrine transformation. Accordingly, deletion of Rb1 and Trp53 along with Pten and Rbl1 (p107) with Ad5-K5-Cre, which targets cells similar to K14-expressing cells, also led to the development of SCLC, supporting the idea that basal cells can serve as a cell of origin for SCLC in the context of a different set of driver lesions (Lázaro et al 2019).…”
Section: Cell Of Origin Of Small Cell Lung Cancer (Sclc)mentioning
confidence: 79%
“…While the neuroendocrine phenotype and common occurrence of RB1 loss in large cell neuroendocrine carcinoma of the lung (LCNEC) have suggested potential ties between this cancer type and SCLC (George et al 2018), a robust mouse model of LCNEC development has not yet been developed. Recently, however, combining Pten deletion alongside Trp53/Rb1/Rbl1 loss, which normally leads to SCLC development (Ng et al 2020), has been shown to generate LCNEC in mouse models (Lázaro et al 2019). Targeting the quadruple knockout to all cell lineages with Ad5-CMV-Cre resulted in a majority of tumors being LCNEC while targeting basal cells with Ad-K5-Cre resulted mostly in SCLC.…”
Section: Cell Of Origin Of Small Cell Lung Cancer (Sclc)mentioning
confidence: 99%
“…We used lung cancer mouse models generated in the laboratory to determine the suitability of the [ 68 Ga]Ga-DOTA-TOC obtained for detection of tumors in vivo by PET imaging. We have used a high-grade neuroendocrine lung cancer animal model rendering Large-Cell Neuroendocrine Carcinoma (LCNEC) 33,34 . LCNEC is an aggressive, poorly differentiated pulmonary neuroendocrine tumor which expresses a high density of surface somatostatin receptors (SSTR).…”
mentioning
confidence: 99%
“…It is widely used in clinical routines for PET imaging of neuroendocrine tumors 37 . The procedure used to label, purify and determine the radiochemical purity of [ 68 Ga]Ga-DOTA-TOC was essentially the same as that used by our group 33 with some adjustments. A solution of 210 ± 5 mg HEPES (Sigma-Aldrich) dissolved in 1 mL of deionized water was transferred into a reaction vial which contained the peptide DOTA-TOC previously dissolved in water.…”
mentioning
confidence: 99%
See 1 more Smart Citation